THE ROLE OF ELECTRONIC WORD OF MOUTH AND THEORY OF PLANNED BEHAVIOR IN SHAPING THRIFT SHOPPING INTENTIONS AMONG GENERATION Z - Nadia Ramadhani Soesmono; Yohanes Thianika Budiarsa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
This research is motivated by the rising popularity of thrift shopping among Generation Z on social media. Grounded in the Theory of Planned Behaviour (TPB), this quantitative study examines the influence of electronic word of mouth (eWOM), attitude, subjective norm, and perceived behavioural control on thrift shopping intention, alongside the mediating role of attitude. Data were collected from 170 respondents in Jabodetabek using convenience sampling and analysed via PLS-SEM. The findings indicate that all proposed relationships are positive and significant. eWOM significantly influences attitude, which successfully mediates the link between eWOM and shopping intention. Among TPB constructs, perceived behavioural control exerts the strongest effect, suggesting Gen Z shops more when feeling capable and confident. Conversely, subjective norm shows the weakest effect. Consequently, thrift businesses should strengthen consumer confidence and encourage positive eWOM through engaging social media content.